AN ANALYSIS OF GRAMMATICAL ERRORS MADE BY THE SECOND GRADE STUDENTS OF SMAN 6 KUNDUR KABUPATEN KARIMUN KEPULAUAN RIAU IN WRITING RECOUNT TEXTS - Saryati, Saryati; Azhar, Fadly; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is aimed to identify both types of grammatical errors and dominant errors made by the second grade students of SMAN 6 Kundur Kabupaten Karimun Kepulauan Riau in writing recount texts. The population as well as the sample (Total Sampling) of this research was the second grade students of SMAN 6 Kundur Kabupaten Karimun Kepulauan Riau. The research findings revealed that all types of grammatical errors and error of formation was the most dominant with 195 errors (54.92%); then, followed by error of omission with 93 errors (26.20%), and error of addition and ordering were below 10%. Error of addition with 34 errors (9.60%) and error of ordering with 33 errors (9.30%). Therefore, it can be concluded that the second grade students of SMAN 6 Kundur Kabupaten Karimun Kepulauan Riau committed the errors because of the influence of their mother tongue, the way of thinking, and generalization of the rule of the target language.Keywords: Error Analysis, Omission, Addition, Formation, ordering.